Pregnancy and delivery in women treated with renal replacement therapy: A literature review - Medved, V.; Bulik, L. (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. The problem of pregnancy and delivery in women with end-stage kidney disease is becoming increasingly important, and the number of such women who are pregnant, receiving kidney replacement therapy, is growing every year. Improvements in dialysis therapy have led to improved obstetric and perinatal outcomes, but the risk of various obstetric and perinatal complications remains extremely high. In this review, we analyzed recently published data on management and outcomes of pregnancy in women with end-stage kidney disease receiving dialysis.